Ellen’s Anorexia in To the Bone Movie (2017) - elsa lubianti; Mia Fitria Agustina; Shofi Mahmudah Budi Utami (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2020)
The research aims to figure out factors causing Ellen, the main character of Noxon’s movie entitled To the Bone, experiences anorexia. The qualitative method is used to collect, interpret, and analyze data. Reading, rereading, collecting, sorting, grouping, interpreting, and analyzing are steps conducted to get the primary data taken from the movie. In addition, the researcher applied Psychology of Literature Theory, Anorexia Nervosa Theory, and Cinematography Theory to answer the research question. The result of this research shows that Ellen’s anorexia is caused by two factors. The first is internal factors (being stress, feeling lonely, and experiencing depression). This factor cannot be seen from other’s viewpoints, but it can be felt by Ellen only. The second is external factors because of her parents’ divorce. The divorce makes Ellen lack of affection and attention. This divorce also causes poor communication between Ellen and her parents. Thus, those two internal factors lead Ellen feels isolated and also makes Ellen’s self-esteem suffered which finally render Ellen experiences anorexia.